2023
DOI: 10.3390/ijerph20020993
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Coping and Psychological Adaptation during the COVID-19 Pandemic

Abstract: This population-based study investigated gender differences in the use of coping strategies and their relationship to anxiety symptoms during the initial COVID-19 lockdown period in the United States. A national online survey was administered between 13 April 2020 and 8 June 2020. The study sample comprised 1673 respondents (66% women). Overall, 46% reported high levels of anxiety, and women experienced significantly (p < 0.001) higher levels of anxiety than men. Women were significantly (p < 0.05) more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…56 Previous studies found that female healthcare workers tend to develop greater physical and emotional stress during COVID-19, and physicians had a higher resilience compared to nurses due to general medical knowledge, education, and training for swift respond to emergencies. [57][58][59][60] Therefore, physicians are better at dealing with poor social adaptation and feelings of isolation, which mitigates the HRPL.…”
Section: Discussionmentioning
confidence: 99%
“…56 Previous studies found that female healthcare workers tend to develop greater physical and emotional stress during COVID-19, and physicians had a higher resilience compared to nurses due to general medical knowledge, education, and training for swift respond to emergencies. [57][58][59][60] Therefore, physicians are better at dealing with poor social adaptation and feelings of isolation, which mitigates the HRPL.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also suggest that high levels of resilience and positive coping strategies could enhance personal growth, which is a desirable outcome of traumatic events 37 , and that greater resilience is associated with fewer symptoms of post-traumatic stress disorder among HCWs 38 . A previous study identified that men and women differ in their coping strategies 39 . The mechanism explaining the gender difference found in our study is not clear and many genetic as well as environmental factors may play a role, possibly also the conjunction of both work and family care related stressors.…”
Section: Discussionmentioning
confidence: 99%
“…However, most problem-focused coping strategies were associated with higher anxiety levels in both men (34%) and women (66%). This might be because it was challenging to organise and ask for practical assistance from others during the lockdown periods when people were forced to remain socially isolated [39]. These findings revealed a link between COVID-19-related anxiety, substance use, and behavioural disengagement, which also implies that when people adopt behavioural disengagement to deal with the COVID-19 threat, they put themselves in the risk categories.…”
Section: Covid-19 and Coping Mechanisms Among Emerging Adultsmentioning
confidence: 92%